GAME TRAINING-BASED COMPETITION, EDUCATION, AND DIGITALIZATION (GT-CED) - Cindyasari Puspagita (PROSEDING, 2022)
Creating new training and development concepts to develop complex training methods is through the GT-CED (Game Training based Competition, Education and Digitalization) method. GT-CED (Game Training based Competition, Education and Digitalization) is the latest method of training to improve employee performance which is packaged in the form of competition-based training games, education, and digitalization. The GT-CED way provides an opportunity for each employee to complete the training time according to the ability of each individual Keywords: game training-based competition, education, and digitalization (GT-CED